2006
DOI: 10.1021/nl060625g
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring of Nematic Liquid Crystals on Viruses with Different Envelope Structures

Abstract: The ordering of synthetic liquid crystals near surfaces is known to be dependent on the nanoscopic structure and chemical functionality of surfaces. In this letter, we report that the orientational ordering of synthetic liquid crystals on surfaces decorated with viruses is also dependent on the structures of the viruses. Each of the four virions investigated had diameters of approximately 100 nm, but three of the viruses (influenza virus, La Crosse virus, and vesicular stomatitis virus) were enveloped in a lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
75
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

7
3

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 19 publications
1
75
1
1
Order By: Relevance
“…[1][2][3] They can be used to image receptor-mediated binding of proteins at surfaces with submicrometer spatial resolution. 4,5 This method is potentially useful because it does not require the use of enzymatic or fluorescent labels, which largely complicate surface-based assays and prevent high levels of multiplexing. 6,7 In addition, this approach does not require the use of complex instrumentation 8 or laborious techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] They can be used to image receptor-mediated binding of proteins at surfaces with submicrometer spatial resolution. 4,5 This method is potentially useful because it does not require the use of enzymatic or fluorescent labels, which largely complicate surface-based assays and prevent high levels of multiplexing. 6,7 In addition, this approach does not require the use of complex instrumentation 8 or laborious techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] What makes LCs useful mainly stems from its optical anisotropy properties such as optical birefringence, which arises from the different refractive indices along two molecular axes of LCs, ie, n o and n e along the ordinary and the extraordinary axes, respectively. The orientations of LCs dominate changes in optical birefringence of LCs, and its control forms a basis of electro-optical switching and LC-based optical biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] One of the most important advantages of LCs-based sensors is that the orientational properties of LCs enable the sensitive amplification and transduction of a series of interactions into optical outputs that are visible to the naked eye between crossed polarizers due to the birefringence of LCs. [7][8][9] When compared with traditional analytical methods, LCs based sensors have many advantages including that they do not require labeling of substrates, complex instrumentations, or tedious sequences of actions. 4,5 Previous studies have shown that the orientational transition of LCs could be coupled to a range of biomolecular interactions such as specific-binding events and enzyme activities at planar interfaces between LCs and the aqueous phases.…”
Section: Introductionmentioning
confidence: 99%